Hsa_circ_0008360 sponges miR-186-5p to target CCND2 to modulate high glucose-induced vascular endothelial dysfunction. Issue 14 (18th July 2021) - Zhu, Qian-Qian; Pu, Xi-Bin; Chen, Tian-Chi; Qiu, Chen-Yang; Wu, Zi-Heng; Tian, Lu; He, Yang-Yan; Wang, Xiao-Hui; Shang, Tao; Wang, Xun; Xiang, Yi-Lang; Li, Dong-Lin; et al.
ABSTRACT: Vascular endothelial dysfunction is associated with the progress of many diseases. Circular RNAs (circRNAs) take part in the dysfunction of vascular endothelium. CircRNA hsa_circ_0008360 (circ_0008360) is dysregulated in high glucose-treated vascular endothelium, while the role and mechanism of circ_0008360 in high glucose-induced dysfunction remain unknown. Human umbilical vascular endothelium cells (HUVEC) were stimulated via high glucose. The abundances of circ_0008360, miR-186-5p and cyclin D2 (CCND2) were examined via quantitative real-time polymerase chain reaction or western blot. Vascular endothelial dysfunction was assessed via cell viability, apoptosis, migration and tube formation. The target relationship between miR-186-5p and circ_0008360 or CCND2 was analyzed via dual-luciferase reporter, RNA pull-down and RNA immunoprecipitation analyses. Circ_0008360 expression was enhanced in high-glucose-treated HUVEC. Circ_0008360 silence mitigated high glucose-induced suppression of viability, migration, tube formation, and increase in apoptosis in HUVEC. MiR-186-5p was sponged by circ_0008360, and miR-186-5p inhibition reversed the effect of circ_0008360 silence on high glucose-induced vascular endothelial dysfunction. MiR-186-5p alleviated high glucose-induced vascular endothelial dysfunction via targeting CCND2. CCND2 interference abolished the aggravated effect of circ_0008360 on high glucose-induced vascular endothelial dysfunction. Circ_0008360 knockdown attenuated high glucose-induced vascular endothelial dysfunction via regulating miR-186-5p and CCND2, indicating circ_0008360 might act as a target for the treatment of vascular endothelial dysfunction. Abbreviations: circRNAs, circular RNAs; HUVEC, human umbilical vascular endothelium cells; CCND2, cyclin D2; XPNPEP3, X-prolyl aminopeptidase 3; ceRNAs, competing endogenous RNAs; miRNAs, microRNAs; qRT-PCR, quantitative real-time polymerase chain reaction; RIP, RNA immunoprecipitation; HIF-1α, hypoxia inducible factor 1 alpha; TLR3, toll-like receptor 3; AKAP12, A-Kinase Anchoring Protein 12; ox-LDL, oxidized low-density lipoprotein; HG, high glucose; NG, normal glucose.